Making a Mobile Educational Robot with a Practical Approach Using Arduino (Future Science, 2021)
The community service held at Vocational High School (SMK) Kawung 1 Surabaya aims to make a prototype of the Mobile Robot Edu. The robot is designed in a modular form and can be programmed according to the user's wishes. The robot consists of a controller module, an ultrasonic sensor module, a line sensor module, an IR receiver module, and a Bluetooth module. So that this educational robot can be used as a line follower robot, namely with a line sensor module on the controller module, this robot also functions as a robot that can be controlled via a remote controller that emits an infrared signal that will be captured by the IR Receiver sensor that is already installed on the controller module. In addition, the robot can be controlled by a smartphone with communication via Bluetooth. Control using a smartphone can be done via the touch screen, through a voice that utilizes Google speech recognition, and through gestures that use the accelerometer sensor found on the smartphone. The outputs of this community service are the Mobile Robot Edu prototype, scientific publications, and publications in the media. So that these outputs can be used for the learning process at SMK Kawung 1 Surabaya.